Salafiyyah/Traditional Islamic Boarding School Research Trends: A Bibliometric Analysis With Vosviewer - Hafidh, Zaini; Nurdin, N (Bestari, 2024)
This study seeks to describe and analyze scientific articles centered on Salafi/traditional Islamic boarding schools (pondok pesantren). The analysis uses VOSviewer with a bibliometric approach, drawing article references from the Google Scholar database via the Publish or Perish application. Character education in pesantren serves as a guiding theme for the search process, resulting in the identification of 200 relevant articles. The study period for the indexed documents spans from 2014 to 2024. The findings focus on identifying and analyzing topics/themes related to character education in pesantren, alongside other data analyses. Keywords associated with Salafi/traditional Islamic boarding schools are linked to 8 clusters and 81 connections, resulting in a total link strength of 93. The analysis of publication trends from 2014 to 2024 indicates that research on character education in pesantren has gained significant popularity among researchers. The most publications occurred in 2023-2024, with 44 articles, while the lowest was in 2015, with 3 articles. The researcher examines the published articles on character education in pesantren and their connections to relevant issues using VOSviewer. This study can serve as a foundation for future research related to pesantren and the broader exploration of topics concerning the pesantren world.